(untitled) (Revista da Faculdade de Odontologia - UPF, 2019)
The present study compared the effectiveness of brushing and over-the-counter tooth-whitening strips on stain removal. Forty bovine teeth were used. Initial color readings were taken, and half of the samples were stained with grape juice for 7 days. The others teeth were used as the control. Both stained and control teeth were randomly separated into 2 groups (n=10) according to the treatment they underwent: whitening strips 2 times/day for 30 minutes for 7 days and mechanical brushing for 1 year using toothpaste. After treatments, new color readings were taken and results of color stability (Î”E) and changes in coordinates (Î”L, Î”a, Î”b) were statistically analyzed (2-way ANOVA, Bonferroni p<.05). Statistical differences were found in Î”E, and all coordinates (p<.05) between control and stained groups, with major changes in the stained group for both treatments. The control group showed greater alteration in Î”b, being higher (p<.05) for bleached teeth, decreasing in yellowness. For stained teeth, Î”a showed the greatest change, decreasing in redness, being higher (p<.05) for bleached teeth. Both treatments were effective for removing stains, and tooth whitening proved to be a more efficient method for removing stains from teeth that had not been subjected to the previous staining.